(untitled) (Medico Legal Update, 2020)
Hypercholesterolemia contributes to the incidence of coronary heart disease which is the leading cause of death in the world 1. Diet modification and hypolipidemic drugs, including herba, one of which is Garcinia mangostana L. will effectively reduce total cholesterol 3. A research a posttest control group design 20, type of research was a laboratory experimental research 15. The population was male white mice aged 3 - 4 weeks weighing 100-200 grams 12. Hypercholesterolemia in male white rats was with MDLT induction ( high - fat diet food ) 7. Data collection of total cholesterol levels measurement used enzymatic spectrophotometer method, data analysis used Variant Analysis statistical test ( ANOVA ) with significance level ? < 0.05 15. The effect of Garcinia mangostana L. rind extract on total cholesterol reduction in white rats was grouped into a negative control group, positive control group and four dose treatment groups 4. Identification of hypercholesterolaemia in white rats was examined for total cholesterol on day 8 16. The effect of Garcinia Mangostana L rind extract on reducing total cholesterol was examined on day 22 3,16 . The results of the examination showed the administration of Garcinia mangostana L. rind extract in all dosage groups effectively reduced total cholesterol levels with a significance level of p < 0.05.